TEMPORARY REDUCTION OF VAT RATES - Minkova, G.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The aim of the article is providing systematic and comprehensive study of the emergency state provoked by coronavirus pandemic and its impact on business, employment and consumption. Taxation could be used as an important tool to influence economic growth that has been declining due to the crisis. However, there are different ways of using taxation in order to resolve economic issues referring to the variety of taxes - direct or indirect, proportionate or progressive and etc. State authorities have to make choices so as to apply the best models of temporary legislative changes in order to help businesses and costumers to face the crisis. In the article, emphasis is put on reduced VAT rate. According to Article 98 of Council Directive 2006/112/EC of 28 November 2006 on the common system of Value Added Tax (VAT), member states may apply either one or two reduced rates only to supplies of goods or services in the categories listed in Annex III. In Bulgaria, new laws have been passed to provide temporarily reduced rates for several supplies. On the one hand, the issue in question is whether the amendments are in compliance with European laws. On the other hand, we have to examine whether the goals of helping businesses and costumers may be achieved by reducing VAT rates. In this connection, the research is focused on similar decisions made by the other member states but at the same time, it shows different approaches taken by them. Two opportunities are put together: first, rate reduction for taxing all the supplies of goods and services for a period of 6 or 18 months and, second, VAT rate reduction for taxing supplies in some branches that are considered to be most important for a particular country.